Applied mathematics a multidisciplinary approach - Lincoln, Lucas (Willford Press, 2018)
Applied mathematics is the application of mathematical techniques in various fields such as engineering, computer science, etc. Computational modeling techniques and actuarial science rely entirely on applied mathematics to analyze data and information. The field of applied mathematics investigates various branches such as artificial intelligence, electromagnetics and meteorology through a multidisciplinary approach. Through this book, the readers would gain knowledge that would broaden their perspective about applied mathematics. It is a complete source of knowledge on the present status of this important field.